Exploring the Perceptions and Experiences of Nurses and Nursing Technicians Regarding the Implementation of a Shared Governance Model in Hafr Al-Batin Hospitals: A Mixed-Methods Study - Maryam Jurayyd Alruwaili; Budoor Lafi Antar Alenazy; Fadia Lafi Antar Alanazi; Nawdhaa Nayyaf Almutairi; Salfah Ali Sroor Almutery; Layla Jried Alrwiyli (International Journal of Medical Toxicology and Legal Medicine, 2024)
Shared governance is a collaborative management model that empowers nurses and nursing technicians to participate in decision-making processes, thereby improving job satisfaction, retention, and patient outcomes. This mixed-methods study aimed to explore the perceptions and experiences of nurses and nursing technicians regarding the implementation of a shared governance model in Hafr Al-Batin hospitals, Saudi Arabia. A convergent parallel design was employed, with concurrent quantitative and qualitative data collection. A total of 150 nurses and nursing technicians were surveyed using the Index of Professional Nursing Governance (IPNG) questionnaire, and 20 participants were purposively selected for semi-structured interviews. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were analyzed using thematic analysis. The findings revealed moderate levels of shared governance, with significant differences based on age, education level, and work experience. Qualitative themes included improved autonomy and empowerment, enhanced collaboration and communication, and challenges in implementation. The integration of quantitative and qualitative findings highlighted the need for targeted interventions to support shared governance implementation, such as leadership training, clear role delineation, and continuous evaluation. This study provides valuable insights into the perceptions and experiences of nurses and nursing technicians regarding shared governance in the Saudi Arabian context, informing strategies for successful implementation and sustainability.